Snail shells as larval habitat of Limatus durhamii (Diptera: Culicidae) in the Yungas of Argentina - Mangudo, Carolina (2017)
The shells of dead snails collect water from rainfalls producing aquatic microenvironments called gastrotelmata. These habitats are small and hold simple detritus based on animal communities, being rotifers and culicids the most studied. Although a high diversity of aquatic microhabitats has been reported as larval habitats of mosquitoes in Argentina, the shell of snails has not been investigated yet. We report the shells of three species of native Megalobulimus genus as larval habitats of a neotropical mosquito and suspected vector of bunyaviruses, Limatus durhamii, and describe these microhabitats in the Yungas forest of Argentina.